Hydrogen Storage in the Carbon Dioxide – Formic Acid Cycle - Cornel Fink; Mickael Montandon-Clerc; Gabor Laurenczy (CHIMIA, 2015)
This year Mankind will release about 39 Gt carbon dioxide into the earth's atmosphere, where it acts as a greenhouse gas. The chemical transformation of carbon dioxide into useful products becomes increasingly important, as the CO2 concentration in the atmosphere has reached 400 ppm. One approach to contribute to the decrease of this hazardous emission is to recycle CO2, for example reducing it to formic acid. The hydrogenation of CO2 can be achieved with a series of catalysts under basic and acidic conditions, in wide variety of solvents. To realize a hydrogen-based charge-discharge device ('hydrogen battery'), one also needs efficient catalysts for the reverse reaction, the dehydrogenation of formic acid. Despite of the fact that the overwhelming majority of these reactions are carried out using precious metals-based catalysts (mainly Ru), we review here developments for catalytic hydrogen evolution from formic acid with iron-based complexes.